The Role of Food Prices and Market Access in Contributing to Hunger in Low-Income Populations - Saada Reuveni (Eximia, 2025)
This article investigates the role of food prices and market access in exacerbating hunger within low-income populations, emphasizing the economic dimensions of food insecurity. Drawing on case studies from Sub-Saharan Africa and Brazil, it highlights how food price volatility and inadequate infrastructure significantly contribute to hunger. High food prices, driven by global disruptions and local inefficiencies, force low-income households to reduce their food intake or opt for less nutritious options, worsening food insecurity. Limited road networks and insufficient storage facilities inflate logistical costs, further impeding food distribution and access. Key findings include Brazil’s Zero Hunger program, which successfully reduced hunger through targeted subsidies, social policies, and infrastructure investments, and the quantitative impact of improved transportation and storage facilities in Sub-Saharan Africa, which stabilized food prices and reduced costs. This research underscores the global significance of addressing hunger amid challenges like climate change and geopolitical disruptions. Policy recommendations include targeted subsidies for staple foods, public-private partnerships to enhance infrastructure, and price stabilization mechanisms. By highlighting the interconnectedness of economic policies, market access, and food security, this study provides policymakers, NGOs, and international organizations with actionable insights to mitigate hunger and build more resilient food systems for vulnerable populations.